2018
DOI: 10.1177/2047487318795194
|View full text |Cite
|
Sign up to set email alerts
|

Associations of leisure-time physical activity with cardiovascular mortality: A systematic review and meta-analysis of 44 prospective cohort studies

Abstract: Leisure-time physical activity shows a linear negative correlation with the risk of cardiovascular mortality regardless of age, gender and the presence of cardiovascular disease or not. However, the cardiovascular benefits of leisure-time physical activity is decreased for those aged over 65 years or those with a history of cardiovascular disease. Moreover, leisure-time physical activity displays more cardiovascular benefits to people followed up for over 10 years than to those followed up for less than 10 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
108
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 73 publications
6
108
2
8
Order By: Relevance
“…The extent to which adults in the UK will revert back to their usual PA regimes once lockdown measures are relaxed is unclear, but the potential for multiple lockdowns being necessary over a protracted period could lead to prolonged periods of low PA in a substantial proportion of the population. This is concerning because it is well established that insufficient levels of PA are associated with poor mental [6] and physical [7,8] health and with premature mortality [9].…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which adults in the UK will revert back to their usual PA regimes once lockdown measures are relaxed is unclear, but the potential for multiple lockdowns being necessary over a protracted period could lead to prolonged periods of low PA in a substantial proportion of the population. This is concerning because it is well established that insufficient levels of PA are associated with poor mental [6] and physical [7,8] health and with premature mortality [9].…”
Section: Discussionmentioning
confidence: 99%
“…Being the first comprehensive meta-analysis on the topic, the findings cannot be directly compared to previous work. Though there has been overwhelming evidence showing that regular physical activity is associated with reduced risk of arterial thrombotic disease [1][2][3], findings on the relationship between physical activity and VTE risk have been mixed in the absence of a pooled analysis. In a recently published narrative review that evaluated the existing epidemiological evidence on the association between physical activity and VTE risk, Evensen and Table 1 colleagues concluded that there might be a modest beneficial effect of physical activity on incident VTE risk [34].…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Physical activity has several health benefits and its inverse and dose-response relationship with cardiovascular disease (CVD) (arterial thrombotic disease) is well established [1][2][3]. Physical activity may reduce vascular risk by exerting Electronic supplementary material The online version of this article (https ://doi.org/10.1007/s1065 4-019-00579 -2) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recent evidences also attest to the benefits of regular physical activity on survival. [4][5][6] Leisure-time physical activity has been negatively correlated with the risk of cardiovascular mortality independently from age, sex and presence or lack of pre-existing cardiovascular disease. 5 Physical fitness has been independently associated with risk of early cardiovascular death in the population aged 50 years or older, which suggests that physical fitness may not only modulate cardiovascular death risk, but that it may also be improved by practising regular physical exercise.…”
mentioning
confidence: 99%
“…[4][5][6] Leisure-time physical activity has been negatively correlated with the risk of cardiovascular mortality independently from age, sex and presence or lack of pre-existing cardiovascular disease. 5 Physical fitness has been independently associated with risk of early cardiovascular death in the population aged 50 years or older, which suggests that physical fitness may not only modulate cardiovascular death risk, but that it may also be improved by practising regular physical exercise. 6 Limited physical activity or, even more worrisome, inability to take a regular walk out of one's home as a consequence of strict quarantine, may be associated with a kaleidoscope of unfavourable metabolic effects that would dramatically increase the risk of many severe and disabling disorders such as diabetes, 7 cancer, 8 osteoporosis 9 and cardiovascular disease.…”
mentioning
confidence: 99%